Proton Magnetic Resonance Spectroscopy for the Early Diagnosis of Parkinson Disease in the Substantia Nigra and Globus Pallidus: A Meta-Analysis With Trial Sequential Analysis - Gu, Wenbin; He, Chen; Chen, Juping; Li, Junchen (Frontiers in Neurology, 2022)
This study aimed to investigate the metabolic changes in globus pallidus (GP) and substantia nigra (SN) during the early stage of Parkinson disease (PD) using magnetic resonance spectroscopy (MRS). PubMed, Embase, Web of Science, and Chinese National Knowledge Infrastructure were searched till November 2018. Eligible trials comparing early metabolic changes in GP and SN in patients with PD vs. controls were included. The mean differences with 95% confidence intervals were estimated with either fixed- or random-effects models using Review Manager 5.3 software. Trial sequential analysis was performed using TSA 0.9.5.10 beta software. Finally, 16 studies were selected from the search. Overall, the N-acetyl aspartate-to-creatine ratio showed a significant difference between patients with early-stage PD and healthy controls. The overall heterogeneity was P < 0.00001, I2 = 94% in GP and P = 0.0002, I2 = 74% in SN. The results revealed that MRS could be a more sensitive imaging biomarker in the diagnosis of early-stage PD. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=125731, registration number: CRD42019125731.